Aerospace series. Shank nuts, serrated, self-locking, in heat resisting steel FE-PA2601 (A286), silver plated on thread. Classification: 1 100 MPa (at ambient temperature) / 650 °C. (31st July 2015) - British Standards Institution,
No abstract available